Kinetics of plasma biomarkers of inflammation and lung injury in surgical patients with or without postoperative pulmonary complications. Issue 4 (April 2017) - Serpa Neto, Ary; Campos, Pedro P.Z.A.; Hemmes, Sabrine N.T.; Bos, Lieuwe D.; Bluth, Thomas; Ferner, Marion; Güldner, Andreas; Hollmann, Markus W.; India, Inmaculada; Kiss, Thomas; Laufenberg–Feldmann, Rita; Sprung, Juraj; et al.
Abstract : BACKGROUND: Postoperative pulmonary complications (PPCs) are common after major abdominal surgery. The kinetics of plasma biomarkers could improve identification of patients developing PPCs, but the kinetics may depend on intraoperative ventilator settings. OBJECTIVE: To test whether the kinetics of plasma biomarkers are capable of identifying patients who will develop PPCs, and whether the kinetics depend on the intraoperative level of positive end-expiratory pressure (PEEP). DESIGN: A preplanned substudy of a randomised controlled trial. SETTING: Operation room of five centres. PATIENTS: Two hundred and forty-two adult patients scheduled for abdominal surgery at risk of developing PPCs. INTERVENTIONS: High (12 cmH2 O) versus low (⩽2 cmH2 O) levels of PEEP. MAIN OUTCOME MEASURES: Individual PPCs were combined as a composite endpoint. Plasma samples were collected before surgery, directly after surgery and on the fifth postoperative day. The levels of the following were measured: tumour necrosis factor (TNF)-α, interleukin (IL)-6 and IL-8, the soluble form of the Receptor for Advanced Glycation End–products (sRAGE), Surfactant Protein (SP)-D, Clara Cell protein (CC)-16 and Krebs von den Lungen 6 (KL6). RESULTS: Blood sampling was complete in 242 patients: 120 patients in the high PEEP group and 122 patients in the low PEEP group. Increases in plasma levels of TNF- IL-6, IL-8 and CC-16, and a decrease in plasma levels of SP-D were greater in patients who developed PPCs; however, the area under the receiver operating characteristic curve was low for all biomarkers. CC-16 was the only biomarker whose level increased more in patients who had received high levels of PEEP. CONCLUSION: In patients undergoing abdominal surgery and at risk of developing PPCs, plasma levels of biomarkers for inflammation or lung injury showed distinct kinetics with development of PPCs, but none of the biomarkers showed sufficient prognostic value. The use of high levels of PEEP was associated with increased levels of CC-16, suggesting lung overdistension. TRIAL REGISTRATION: The PROVHILO trial, including this substudy, was registered at clinicaltrials.gov (NCT01441791). Abstract : Supplemental Digital Content is available in the text